Relationship between vastus medialis Hoffmann reflex excitability and knee extension biomechanics during different tasks in women with patellofemoral pain - Waiteman, Marina Cabral [UNESP]; Botta, Ana Flavia Balotari [UNESP]; Perez, Vitória Ozores [UNESP]; de Oliveira Silva, Danilo; Pazzinatto, Marcella Ferraz; Magalhães, Fernando Henrique [UNESP]; de Azevedo, Fábio Mícolis [UNESP]; Briani, Ronaldo Valdir [UNESP] (My University, 2022)
Background: Impaired knee extension biomechanics and spinal excitability have been reported in women with patellofemoral pain, but their relationship has not been explored. A significant relationship between them could indicate the need for investigating the potential benefits of disinhibitory interventions for women with patellofemoral pain. Thus, this study aimed to investigate the relationship between vastus medialis Hoffmann reflex and (1) maximal isometric, concentric and eccentric knee extensor strength and rate of torque development; (2) knee extensor torque steadiness; and (3) knee extensor moment during functional tasks; in women with patellofemoral pain. Methods: Spinal excitability of twenty-four participants was assessed by the amplitude of maximal vastus medialis Hoffmann reflex. Knee extensor strength, rate of torque development and torque steadiness were assessed using an isokinetic dynamometer. Knee extensor moment during step-down and stair descent tasks were obtained using a three-dimensional motion analysis system. Findings: A moderate negative relationship was found between vastus medialis Hoffmann reflex and knee extensor torque steadiness (r = −0.35; p = 0.05); whereas a moderate positive relationship was found with maximal isometric knee extensor strength (r = 0.37; p = 0.044). No significant relationships were found between vastus medialis Hoffmann reflex and the other variables. Interpretation: Our findings provide insight on the relationship between spinal excitability and neuromuscular control of maximal and submaximal isometric torque production in women with patellofemoral pain. Conversely, spinal excitability does not seem to be related with dynamic torques and moments of the knee extensors in women with patellofemoral pain.
Keywords: Anterior knee pain; Quadriceps muscle; Spinal reflex excitability; Torque variability